Image-based detection and tracking of resident space objects for situational awareness - Zhang, Rangya (Nanyang Technological University, 2024)
Space Situational Awareness (SSA) is crucial for ensuring the safety and sustainability of space operations. With the exponential increase in the number of Resident Space Objects (RSOs), including operational satellites, defunct satellites, and space debris, the need for advanced and effective detection and tracking technologies has become more urgent than ever. Existing algorithms often struggle with the unique challenges posed by the space environment, such as low Signal-to-Noise Ratio (SNR), high-velocity objects, small target sizes, and highly variable environmental conditions. These challenges highlight the necessity for more sophisticated methodologies capable of addressing the specific conditions of space.